Positive electrode current collector, secondary battery, and electric device

By using a binder with a structure containing carboxyl and amide groups, a conductive agent and a water-absorbing agent in the positive electrode current collector, the double hydrogen bond is formed, which solves the problem of poor conductivity of the positive electrode active material and improves the circulation performance of the secondary battery and thermal stability reduces the internal resistance of the battery and extends the service life of the battery.

CN119181807AActive Publication Date: 2024-12-24SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411308693.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The poor conductivity of existing positive electrode active materials leads to insufficient cycling performance of lithium-ion secondary batteries, and high DCR (battery internal resistance), which affects the service life and performance of the battery.

Method used

A positive electrode current collector is adopted, which includes a matrix layer and a coating, which contains a binder with a structural formula containing a carboxyl group and an amide group, and combines a conductive agent and an anti-absorbent agent to form a stronger bonding force through double hydrogen bonds and Conductivity, reduces thermal gravity loss, improves thermal stability, and controls coating thickness and component ratios to optimize bonding and electrochemical properties.

Benefits of technology

It effectively improves the adhesion and conductivity of the positive electrode sheet, reduces the diaphragm resistance, significantly improves the circulation performance and thermal stability of the secondary battery, reduces DCR, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181807A_ABST
    Figure CN119181807A_ABST
Patent Text Reader

Abstract

The invention discloses a positive current collector, a secondary battery and an electric device, and belongs to the technical field of batteries, the positive current collector comprises a matrix layer and a coating arranged on at least one surface of the matrix layer, the coating comprises a binder, and the structural formula of the binder contains carboxyl and at least one amide group; the positive current collector meets the condition that T300-T450 is greater than or equal to 9% and less than or equal to 22%; wherein T300 is the peak value of the TG spectrum of the positive electrode current collector at 300 DEG C; and T450 is the peak value of the TG spectrum of the positive current collector at 450 DEG C. The positive current collector disclosed by the invention effectively improves the cycle performance of the secondary battery and reduces the DCR (Direct Current Ratio).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode current collector, a secondary battery and an electrical device. Background Art

[0002] Secondary batteries have outstanding advantages such as high energy density, high power density, long service life and no memory effect. They have been widely used in consumer electronics, home appliances, aerospace, electric vehicles and other fields.

[0003] Positive electrode active materials, especially lithium iron phosphate, are widely used in the preparation of lithium-ion secondary batteries because of their large discharge capacity, high safety, low price and no environmental pollution. However, their poor conductivity has seriously hindered their practical application, resulting in insufficient cycle performance.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present application is to overcome the shortcomings of the prior art and provide a positive electrode current collector, a secondary battery and an electrical device, which can effectively improve the cycle performance of the secondary battery and reduce the DCR.

[0006] To achieve the above-mentioned object, the first aspect of the present application provides a positive electrode current collector, the positive electrode current collector comprising a substrate layer and a coating disposed on at least one surface of the substrate layer, the coating comprising a binder, the structural formula of the binder containing a carboxyl group and at least one amide group;

[0007] The positive electrode current collector satisfies: 9%≤△T 300 -△T 450 ≤22%;

[0008] Among them, △T 300 is the peak value of the TG spectrum of the positive electrode current collector at 300° C.;

[0009] △T 450 It is the peak value of the TG spectrum of the positive electrode current collector at 450°C.

[0010] As an embodiment of the present application, the binder comprises a structural formula as shown in Formula I:

[0011]

[0012] In formula I, y:x=(5~25):(75~95), 20000≤x≤30000.

[0013] As an embodiment of the present application, the mass percentage of the binder in the coating is 45% to 50%.

[0014] As an embodiment of the present application, the coating further includes an anti-water absorption agent, and the anti-water absorption agent includes at least one of calcium hydroxide, calcium oxide, sodium hydroxide, calcium chloride, and silica gel.

[0015] As an embodiment of the present application, the mass percentage of the anti-water absorption agent in the coating is 2% to 10%.

[0016] As an implementation scheme of the present application, the mass ratio of the binder to the anti-water absorption agent is (6-10):1.

[0017] As an embodiment of the present application, the coating further includes a conductive agent, and the mass percentage of the conductive agent in the coating is 40% to 45%.

[0018] As an embodiment of the present application, the thickness of the coating layer is 0.5 μm to 5 μm.

[0019] As an embodiment of the present application, the sheet resistance of the positive electrode current collector is 55 mΩ to 185 mΩ.

[0020] A second aspect of the present application provides a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises the positive electrode collector described above and a positive electrode active material layer disposed on at least one surface of the positive electrode collector.

[0021] As an implementation scheme of the present application, the bonding force of the positive electrode sheet is 17.5 N / m to 28 N / m.

[0022] A third aspect of the present application provides an electrical device, comprising the secondary battery described above.

[0023] The beneficial effect of the present application is that the positive electrode current collector described in the present application comprises a substrate layer and a coating disposed on at least one surface of the substrate layer, wherein the coating contains a binder having a structural formula containing a carboxyl group and at least one amide group and satisfies: 10%≤△T 300 -△T 450 ≤20%; can effectively reduce thermogravimetric loss, improve the thermal stability of the positive electrode current collector, the binder can hydrate with the conductive agent to form a double hydrogen bond, effectively improve the bonding force between the positive electrode current collector and the positive electrode active material layer, can better connect the substrate layer and the positive electrode active material, effectively improve the bonding force and conductivity of the positive electrode sheet, and effectively reduce the contact resistance between the bottom coating and the positive electrode active material layer, effectively improve the cycle performance of the secondary battery, and reduce DCR. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 TG spectra of Example 1 and Comparative Examples 1 and 2.

[0025] Figure 2 The diaphragm resistance diagrams of Example 1 and Comparative Examples 1 and 2 are shown.

[0026] Figure 3 It is the bonding force diagram of Example 1, Comparative Examples 1 and 2.

[0027] Figure 4 It is the cycle performance diagram of Example 1 and Comparative Examples 1 and 2.

[0028] Figure 5 These are the DCR diagrams of Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0030] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0031] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0032] In the present application, there is no particular limitation on the specific stirring, mixing, ball milling and roller pressing treatment methods, and those skilled in the art can select appropriate specific stirring, mixing, ball milling and roller pressing treatment methods according to actual needs.

[0033] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.

[0034] The embodiment of the present application provides a positive electrode current collector, the positive electrode current collector comprising a substrate layer and a coating disposed on at least one surface of the substrate layer, the coating comprising a binder, the structural formula of the binder containing a carboxyl group and at least one amide group;

[0035] The positive electrode current collector satisfies: 9%≤△T300 -△T 450 ≤22%, for example, it may be 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22% or a range consisting of any two of these values;

[0036] Among them, △T 300 is the peak value of the TG spectrum of the positive electrode current collector at 300° C.;

[0037] △T 450 It is the peak value of the TG spectrum of the positive electrode current collector at 450°C.

[0038] The positive electrode current collector described in the present application comprises a substrate layer and a coating disposed on at least one surface of the substrate layer, wherein the coating contains a binder having a structural formula containing a carboxyl group and at least one amide group and satisfies: 10%≤△T 300 -△T 450 ≤20%; can effectively reduce thermogravimetric loss, improve the thermal stability of the positive electrode current collector, the binder can hydrate with the conductive agent to form a double hydrogen bond, effectively improve the bonding force between the positive electrode current collector and the positive electrode active material, can better connect the substrate layer and the positive electrode active material layer, effectively improve the bonding force and conductivity of the positive electrode sheet, and effectively reduce the contact resistance between the bottom coating and the positive electrode active material layer, effectively improve the cycle performance of the secondary battery, and reduce DCR.

[0039] In one embodiment, the structural formula of the binder is as shown in Formula I:

[0040]

[0041] In formula I, y:x=(5~25):(75~95), 20000≤x≤30000.

[0042] The present application adopts a binder shown in Formula I, which contains a carboxyl group and at least one amide group in its molecular structure, which can not only form hydrogen bonds with the hydroxyl groups on the surface of the conductive agent, but also form intermolecular hydrogen bonds, effectively improving the bonding force between the positive electrode collector and the positive electrode active material, while effectively reducing thermogravimetric loss, improving the thermal stability of the positive electrode collector, improving the safety of the secondary battery, effectively improving the cycle performance of the secondary battery, and reducing DCR.

[0043] Among them, the ratio of the glycine amide segment to the acrylic acid segment in the binder shown in Formula I is (5-25): (75-95), and x is 20000-30000. The binder not only has extremely high thermal stability, reduces the thermogravimetric loss of the positive electrode collector, and improves the safety of the secondary battery, but also can provide better bonding between the substrate layer and the positive electrode active material layer, further improve the binder and conductivity, thereby further improving the cycle performance and reducing the DCR.

[0044] In one embodiment, the positive electrode current collector satisfies: 13%≤ΔT 300 -△T 450 ≤20%.

[0045] In one embodiment, the mass percentage of the binder in the coating is 45% to 50%, for example, it can be 45%, 46%, 47%, 48%, 49%, 50% or a range consisting of any two values ​​therein. By controlling the content of the binder in the coating within this range, ΔT 300 -△T 450 value, avoiding excessive thermogravimetric loss of the positive electrode collector, improving safety, and maintaining good adhesion while improving conductivity.

[0046] In one embodiment, the coating further includes an anti-water absorption agent, and the anti-water absorption agent includes at least one of calcium hydroxide, calcium oxide, sodium hydroxide, calcium chloride, and silica gel.

[0047] In one embodiment, the mass percentage of the anti-water absorption agent in the coating is 2% to 10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of these values. By controlling the amount of the anti-water absorption agent within this range, the moisture content of the electrode is reduced and the battery performance is improved.

[0048] In one embodiment, the mass ratio of the binder to the anti-water absorption agent is (6-10):1, for example, it can be 6:1, 7:1, 8:1, 9:1, 10:1 or a range consisting of any two values ​​therein. By controlling the mass ratio of the binder to the anti-water absorption agent within this range, the electrode bonding ability and moisture content are taken into account.

[0049] In one embodiment, the coating further includes a conductive agent, and the mass percentage of the conductive agent in the coating is 40% to 45%, for example, it can be 40%, 41%, 42%, 43%, 44%, 45% or a range consisting of any two values ​​therein. By controlling the content of the conductive agent within this range, the conductive agent can better form hydrogen bonds with the adhesive to improve the bonding force.

[0050] In one embodiment, the conductive agent comprises at least one of conductive carbon black, conductive graphite, carbon nanotubes, and graphene.

[0051] In one embodiment, the thickness of the coating is 0.5 μm to 5 μm, for example, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or a range consisting of any two of these values.

[0052] In one embodiment, the coating has a thickness of 1 μm to 3 μm.

[0053] In one embodiment, the thickness of the base layer is 12 μm to 15 μm, for example, 12 μm, 13 μm, 14 μm, 15 μm or a range consisting of any two values ​​therein.

[0054] In one embodiment, the type of the base layer is not particularly limited, and the base layer can be any material known to be suitable for use as a base layer.

[0055] In one embodiment, the substrate layer includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.

[0056] In one embodiment, the substrate layer is a metal material. In one embodiment, the positive electrode current collector is aluminum.

[0057] There is no particular limitation on the form of the substrate layer. When the substrate layer is a metal material, the substrate layer may be in the form of metal foil, metal cylinder, metal strip, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the substrate layer is a carbon material, the substrate layer may be in the form of, but not limited to, carbon plate, carbon film, carbon cylinder, etc.

[0058] In one embodiment, the sheet resistance of the positive electrode current collector is 55mΩ to 185mΩ, for example, it can be 55mΩ, 65mΩ, 75mΩ, 85mΩ, 95mΩ, 105mΩ, 115mΩ, 125mΩ, 135mΩ, 145mΩ, 155mΩ, 165mΩ, 175mΩ, 185mΩ or a range consisting of any two of these values.

[0059] In one embodiment, the preparation method of the binder is:

[0060] The pH of the polyacrylic acid solution is adjusted to 5.5-6 with a pH adjuster, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added, stirred evenly, and then glycineamide hydrochloride is added to react to obtain a binder.

[0061] The reaction principle of the binder is as follows:

[0062]

[0063] In one embodiment, the mass concentration of the polyacrylic acid solution is 0.1-10%, for example, it can be 0.1%, 0.2%, 0.5%, 1%, 2%, 4%, 5%, 6%, 8%, 10% or a range consisting of any two values ​​therein.

[0064] In one embodiment, the mass ratio of the polyacrylic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and N-hydroxysuccinimide is 100:(15-25):(10-15), for example, it can be 100:15:10, 100:18:12, 100:20:15, 100:25:10 or a range consisting of any two of the values.

[0065] In one embodiment, the molar ratio of polyacrylic acid to glycineamide hydrochloride is (8-12):1, for example, 8:1, 9:1, 10:1, 11:1, 12:1 or a range consisting of any two of these values.

[0066] In one embodiment, the pH adjuster includes at least one of sodium hydroxide solution, potassium hydroxide solution, and ammonia water.

[0067] In one embodiment, the reaction temperature is 20-40°C, for example, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C, 38°C, 40°C or a range consisting of any two of these values.

[0068] In one embodiment, the reaction time is 12 to 72 hours, for example, it can be 12 hours, 16 hours, 20 hours, 24 hours, 30 hours, 36 hours, 40 hours, 48 ​​hours, 52 hours, 60 hours, 64 hours, 68 hours, 72 hours or a range consisting of any two values ​​therein.

[0069] One embodiment of the present application provides a secondary battery, comprising a positive electrode plate and a negative electrode plate, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, and the positive electrode collector comprises the positive electrode collector described above.

[0070] In one embodiment, the bonding force of the positive electrode sheet is 17.5 N / m to 28 N / m. The bonding force of the positive electrode sheet is the bonding force between the positive electrode active material layer and the positive electrode current collector.

[0071] In one embodiment, the positive electrode plate includes a positive electrode active material, and the positive electrode active material can be selected from sodium iron composite oxide, sodium cobalt composite oxide, sodium manganese composite oxide, sodium nickel composite oxide, sodium nickel titanium composite oxide, sodium nickel manganese composite oxide, sodium iron manganese composite oxide, sodium nickel cobalt manganese composite oxide, sodium iron phosphate compound, sodium manganese phosphate compound, sodium cobalt phosphate compound, lithium nickel cobalt manganese oxide, lithium phosphate, etc. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more.

[0072] In one embodiment, the secondary battery includes a positive electrode plate, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes carbon-coated lithium iron phosphate, the positive electrode collector includes a substrate layer and a coating arranged on at least one surface of the substrate layer, the coating includes a binder, and the structural formula of the binder contains a carboxyl group and at least two amide groups.

[0073] The structural formula of the binder contains at least two amide groups, which enable double hydrogen bonds to be formed between the molecular chains of the binder. Double hydrogen bonds can also be formed by hydration of hydroxyl groups wrapped on the surface of the lithium iron phosphate carbon layer and the surface of the conductive agent, thereby increasing the bonding force between the current collector and the positive electrode active material and improving the electrochemical performance of the positive electrode sheet.

[0074] In one embodiment, the secondary battery further includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0075] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0076] In one embodiment, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel structure lithium titanate Li 4 Ti 5 O 12 , at least one of Li-Al alloy and metallic lithium.

[0077] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited as long as the effect of the present application is not significantly impaired.

[0078] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.

[0079] In one embodiment, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above-mentioned diaphragm can be used alone or in any combination.

[0080] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0081] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0082] In some embodiments, the type of the electrolyte is not specifically limited. The electrolyte includes an electrolyte salt and an organic solvent. The specific types of the electrolyte salt and the organic solvent are not specifically limited and can be selected according to actual needs. The electrolyte may also include additives. The types of the additives are not particularly limited and may be film-forming additives for the positive electrode and / or the negative electrode, or additives that can improve certain properties of the battery, such as additives that improve the high or low temperature performance of the battery.

[0083] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0084] An embodiment of the present application provides an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.

[0085] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0086] The present application is further described below with specific embodiments:

[0087] Example 1

[0088] A method for preparing a secondary battery comprises the following steps:

[0089] (1) Preparation of binder: 1 g of polyacrylic acid was added to water to prepare a polyacrylic acid solution with a mass concentration of 1%, the pH was adjusted to 5.8 with sodium hydroxide, 0.2 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and 0.12 g of N-hydroxysuccinimide were added, and the mixture was stirred evenly. 0.23 g of glycineamide hydrochloride was added, and the mixture was concentrated, dialyzed with a dialysis bag, and dried to obtain a binder (hereinafter referred to as PAA-GA).

[0090] (2) Preparation of positive electrode sheet: Conductive carbon black SP, the binder of step (1), and calcium hydroxide are prepared into a coating slurry in a mass ratio of 47:50:5; an aluminum foil with a thickness of 13 μm is taken, the coating slurry is applied on the surface of the aluminum foil, and dried to form a positive electrode current collector;

[0091] Lithium iron phosphate, conductive carbon black SP, polyvinylidene fluoride, and solvent N-methylpyrrolidone in a mass ratio of 8:1:1 are mixed to form a uniform electrode slurry, and then the slurry is evenly coated on the positive electrode collector, and then rolled after drying at 110° C. to obtain a positive electrode sheet;

[0092] (3) Preparation of negative electrode sheet: Graphite, polyvinylidene fluoride, conductive carbon black SP, and solvent N-methylpyrrolidone in a mass ratio of 8:1:1 were mixed to form a uniform electrode slurry, and then the slurry was evenly coated on a copper foil with a thickness of 8 μm, dried at 110° C., and then rolled to obtain a negative electrode active material layer;

[0093] (4) Assembly of secondary battery: The separator is a polypropylene porous membrane; dimethyl carbonate and ethylene carbonate are mixed in a mass ratio of 4:6, and lithium hexafluorophosphate is added thereto as an electrolyte solution, wherein the molar concentration of lithium hexafluorophosphate is 1 mol / L. The positive electrode sheet, the negative electrode sheet, the separator and the electrolyte solution are assembled into a button cell to obtain a secondary battery.

[0094] The specific parameters of the positive electrode current collector of this embodiment are shown in Table 1.

[0095] Embodiments 2 to 5

[0096] The difference between Examples 2 to 5 and Example 1 is that Examples 2 to 5 change the amount of PAA-GA added.

[0097] Embodiments 6 to 10

[0098] The difference between Examples 6 to 10 and Example 1 is that Examples 6 to 10 change the amount of calcium hydroxide added.

[0099] Examples 11 to 13, Comparative Examples 3 to 4

[0100] The difference between Examples 11 to 13 and Comparative Examples 3 to 4 and Example 1 is that the ratio of x and y in the PAA-GA structural formula is adjusted by changing the amount of glycineamide hydrochloride added.

[0101] Embodiments 14 to 17

[0102] The difference between Examples 14 to 17 and Example 1 is that Examples 14 to 17 use polyacrylic acid with different molecular weights to change x in the PAA-GA structural formula.

[0103] Embodiments 18 to 20

[0104] The difference between Examples 18 to 20 and Example 1 is that the thickness of the coating is changed in Examples 18 to 20.

[0105] Comparative Example 1

[0106] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses polyacrylic acid (hereinafter referred to as PAA) as a binder.

[0107] Comparative Example 2

[0108] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses SBR as a binder.

[0109] Table 1

[0110]

[0111]

[0112] Test Case

[0113] 1.TG spectrum: "Reference standard: GB / T 27761-2011 Test method for weight loss and residual amount of thermogravimetric analyzer, test temperature: 30~500℃, 10℃ / min, upper limit temperature: 800℃; test atmosphere: nitrogen / air; test crucible: aluminum crucible / alumina crucible.

[0114] Among them, the TG test spectra of Example 1, Comparative Examples 1 and 2 are as follows Figure 1 shown.

[0115] 2. Sheet resistance of positive electrode current collector: Test area: 15.4025mm 2; Trigger pressure: 0.4t; Sampling time: 10s; Test parallel samples: 10; First, test the no-load diaphragm resistance values ​​R1, R2, and R3 three times, then take the diaphragm resistance values ​​R1~R10 at 10 different locations of the electrode, and calculate the diaphragm resistance value = (R1+R2…+R10) / 10-(r1+r2+r3) / 3.

[0116] Among them, the film resistance of Example 1, Comparative Examples 1 and 2 is as follows: Figure 2 shown.

[0117] 3. Adhesion: Sample size: 40mm*400mm; Sensor: 50N; Default peeling length: 150mm; Test settings: full scale 50N; Load limit 40N; Stroke limit 150mm; Stroke speed 50mm / min; Change point: 150mm; Data processing settings: Initial stroke 40mm, end stroke 120mm; Upper limit 50N, lower limit 0N; Test 3 parallel samples; Record the average tension F1, F2, F3 (unit: N) of the tensile testing machine within the stroke of 40-120mm, Adhesion = (F1+F2+F3) / 0.04 / 3 (unit: N / m).

[0118] Among them, the bonding strength of Example 1, Comparative Examples 1 and 2 is as follows: Figure 3 shown.

[0119] 4. Cycle performance: 45℃ cycle performance test: At 45℃, the battery is tested for charge and discharge cycles at a charge and discharge rate of 1C / 1C in the range of 2.5-3.8V, and the battery's first-week discharge capacity and the discharge capacity after 500 cycles are recorded, and the capacity retention rate of 500 cycles is calculated. The capacity retention rate of 500 weeks = 500-week discharge capacity / first-week discharge capacity*100%.

[0120] Among them, the cycle performance of Example 1, Comparative Examples 1 and 2 is as follows: Figure 4 shown.

[0121] 5.DCR: At 25°C, adjust the battery to 10%, 50%, and 90% SOC, and charge at 4C current for 10s, record the voltage rise △V and current I, and calculate DCR, DCR = △V / I.

[0122] Among them, the DCR of Example 1, Comparative Examples 1 and 2 is as follows: Figure 5 shown.

[0123] Table 2

[0124]

[0125]

[0126] As can be seen from Table 2, the positive electrode current collector described in the present application can significantly improve the bonding force and conductivity, thereby significantly reducing the membrane resistance, improving the bonding force, and further significantly improving the cycle performance of the secondary battery and reducing the DCR.

[0127] By comparing Example 1 with Comparative Examples 1 to 2, it can be seen that the binder described in the present application can significantly improve the bonding force and conductivity, thereby significantly reducing the membrane resistance, improving the bonding force, and further significantly improving the cycle performance of the secondary battery and reducing the DCR.

[0128] By comparing Example 1 with Comparative Examples 3 to 4, it can be seen that the present invention controls 9%≤△T 300 -△T 450 ≤22%, further improving the cycle performance and reducing DCR.

[0129] By comparing Examples 1 to 5, it can be seen that the present application can balance the bonding force and electrochemical performance, reduce processing risks, and avoid film release during processing by controlling the content of the binder in the coating to 45% to 50%.

[0130] Comparing Examples 1, 6 to 10, it can be seen that the present application further reduces the DCR by controlling the content of the anti-water absorption agent in the coating to 2% to 10%.

[0131] By comparing Example 1 with Examples 14 to 17, it can be seen that the present application effectively improves the bonding force, improves the cycle performance of the secondary battery, and reduces the DCR by controlling x in the binder structure formula to be 20,000 to 30,000.

[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A positive electrode current collector, characterized in that: The positive electrode current collector comprises a base layer and a coating disposed on at least one surface of the base layer, wherein the coating comprises a binder, and the structural formula of the binder contains a carboxyl group and at least one amide group; The positive electrode current collector satisfies: 9%≤△T 300 -△T 450 ≤22%; Among them, △T 300 is the peak value of the TG spectrum of the positive electrode current collector at 300° C.; △T 450 It is the peak value of the TG spectrum of the positive electrode current collector at 450°C.

2. The positive electrode current collector according to claim 1, characterized in that: The binder comprises a structural formula as shown in Formula I: In formula I, y:x=(5~25):(75~95), 20000≤x≤30000.

3. The positive electrode current collector according to claim 1, characterized in that: The mass percentage of the binder in the coating is 45% to 50%.

4. The positive electrode current collector according to claim 1, characterized in that: The coating also includes an anti-water absorption agent, which includes at least one of calcium hydroxide, calcium oxide, sodium hydroxide, calcium chloride, and silica gel.

5. The positive electrode current collector according to claim 4, characterized in that: The mass percentage of the anti-water absorption agent in the coating is 2% to 10%.

6. The positive electrode current collector according to claim 4, characterized in that: The mass ratio of the binder to the anti-water absorption agent is (6-10):

1.

7. The positive electrode current collector according to claim 1, characterized in that: The coating also includes a conductive agent, and the mass percentage of the conductive agent in the coating is 40% to 45%.

8. The positive electrode current collector according to claim 1, characterized in that: Satisfy at least one of the following conditions: (1) The thickness of the coating is 0.5 μm to 5 μm; (2) The sheet resistance of the positive electrode current collector is 55 mΩ to 185 mΩ.

9. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode collector according to any one of claims 1 to 8 and a positive electrode active material layer arranged on at least one surface of the positive electrode collector.

10. The secondary battery according to claim 9, characterized in that: The bonding force of the positive electrode plate is 17.5 N / m to 28 N / m.

11. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9 or 10.

Citation Information

Patent Citations

  • BINDER, NEGATIVE ELECTRODE SLURRY INCLUDING THE SAME, NEGATIVE ELECTRODE and RECHARGEABLE BATTERY

    CN111864208A

  • Positive electrode binder composition and positive electrode

    CN118335989A

  • Binder composition for secondary battery

    WO2021253672A1